The Fragmented Landscape of Stroke Epidemiology in Indonesia - Ikhsan, Maulana; Wahyuni, Hendra (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Indonesia encounters substantial obstacles in stroke surveillance, as indicated by Riskesdas, BPJS, and hospital registries. The disconnected and inconsistent data that is gathered from these sources is the root cause of these challenges. When there are inconsistencies in case definitions, reporting, and geographical biases, it is challenging to conduct an accurate burden assessment and develop appropriate policies. The analysis of stroke epidemiology data from 2007 to 2023 in this study reveals significant deficiencies. These deficiencies encompass discrepancies in diagnostic accessibility, underrepresentation in hospital registries, and methodological inconsistencies in national surveys. One of the recommendations is the integration of a National Stroke Registry with BPJS to facilitate real-time data transmission. Additionally, the standardization of reporting through the application of WHO standards and ICD-11 classification, as well as the enhancement of rural documentation through the application of professional development and digital technologies, are additional recommendations. The resolution of these issues would enhance the precision of data, facilitate the application of evidence-based decision-making, and enhance the equity of stroke care in all of Indonesia's numerous regions.